2017
DOI: 10.1111/jopr.12575
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Fracture Resistance and the Time Required for Two Different Fiber Post Removal Systems

Abstract: Compared to the removal kit, removal of the fiber posts with an ultrasonic tip decreases the fracture resistance of the roots, although significantly more time is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
6

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
0
25
0
6
Order By: Relevance
“…The use of ultrasound alone also entails a risk of reducing the tooth's mechanical resistance, probably because of heat production or incipient radicular cracks. This latter drawback appears to be less prevalent when using drilling techniques .…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound alone also entails a risk of reducing the tooth's mechanical resistance, probably because of heat production or incipient radicular cracks. This latter drawback appears to be less prevalent when using drilling techniques .…”
Section: Discussionmentioning
confidence: 99%
“…Aydemir, Arukaslan, Sarıdağ, Kaya‐Büyükbayram, and Ylıdıran () compared the efficiencies of the D.T. Light fiber post removal kit and stainless steel ultrasonic tips for removal of quartz fiber posts; they found that post removal with ultrasonic tips took longer than did removal with kits.…”
Section: Discussionmentioning
confidence: 99%
“…In certain cases, a fibre post must be removed in order to re‐gain access to the apical part of the root canal for endodontic retreatment . In the recent times, there have only been a few studies assessing the risks of removal procedures, working time and effectiveness of fibre post removal . Additionally, Scotti et al .…”
Section: Discussionmentioning
confidence: 99%
“…carbon, quartz, zirconium or glass) embedded in an epoxy‐resin matrix .The structure provides a modulus of elasticity similar to that of dentine which makes root fracture more unlikely than for teeth restored with metal posts . Several devices and techniques are available and have been proposed for the removal of different types of posts, including ultrasonics, sonics, round burs, as well as specially designed kits of burs, for example the DT‐Post removal kit (VDW‐Antaeos, Munich, Germany) . This kit consists of a pilot drill which creates an initial hole into the coronal portion of the post, and is followed by a carbide bur to drill out the entire post.…”
Section: Introductionmentioning
confidence: 99%